Internal and external obstacles facing medium and large enterprises in Rusayl Industrial Estates in the Sultanate of Oman - Azzah Al-Maskari; Majed Al-Maskari; Mansoor Alqanoobi; Siraj Kunjumuhammed (Journal of Global Entrepreneurship Research, 2019)
Industrial Estates are significant for the growth of any economy. In this research, the business mangers' perceptions of the internal and external obstacles facing medium and large enterprises in the Industrial Estates are collected and analyzed. The research is conducted with special reference to the Rusayl Industrial Estate (RIE), a prominent Industrial Estate in Oman. A structured questionnaire was administered to a sample of 42 enterprises in the RIE. The survey discovered that medium enterprises reported more obstacles, both internal and external, compared to larger enterprises. Among a variety of external barriers, the lack of raw materials, the lack of skilled workers, visas for foreign workers and the high interest rate of business loans, are at the top of the list. The most significant internal obstacles are competitive pressure in the market, difficulty of external marketing, high labor cost and high operating cost. Some challenges, such as lack of skilled workers and difficulty getting visas for foreign workers are common to medium and large enterprises alike. The study emphasized the need for strategic intervention by regulatory agencies primarily aimed to mitigate the various challenges and provide a conducive environment for enterprises to develop.
Keywords: 650; Industrial estate; External and internal barriers; Medium and large enterprises